Odpowiedzi

Najlepsza Odpowiedź!
2009-10-18T12:24:54+02:00
A)2√3*7√3=14*3=42
b) (2√7)²=4*7=28
c)√2*√3=√6
d)2√%*3√2=6*√10
e)∛15*(2∛15)=15^⅓*4*15^⅔=4*15^(⅔+⅓)=4*15=60
f)3∛7*6∛2=3*7^(⅓)*6*2^(⅓)=18*(7*2)^(⅓)=18∛14
g)(9*3)/4=27/4=6 3/4
h) 2√(6/2)=2√3
i)4/5√(50/2)=4/5√25=(4/5)*5=4
j)42*√(24/6)=41*√4=42*2=84
k)(1/6)*∛(24/3)=(1/6)*∛8=(1/6)*2=⅓
z36
a) √(32/2)+√(2/2)=√16+1=5
b)√(27/3)-√(12/3)=√9-√4=3-2=1
c) ∛(16/2)+∛(54/2)=∛8+∛27=2+3=5
d) √(2*8)+√(2*50)=√16+√100=4+10=14
e) √(50/2)+(1/2)*√(72/2)=√25+(1/2)√36=5+(1/2)*6=5+3=8
f) 4∛(16/250)-∛(54/250)=4∛(8/125)-∛(27/125)=4*(2/5)-(3/5)=
(8/5)-(3/5)=1
g)dzielę każdy składnik licznika przez mianownik , skracam ułamki przez 10
√(25/100)-√(16/100)-√(4/100)=5/10-4/10-2/10=-1/10
h) ∛(9*24)-∛(3*9)=∛216-∛27=6-3=3
1 5 1
2009-10-18T12:48:26+02:00
34)
e)=3pierwiastki√15×8×3pierwiastki√225=8×3pierwiastki√3375=8×15=120
f)=18×3pierwiastki√14
g)=(3√3/2)²=9×3/4=27/4
h)=2√3
i)=4√50/5√2=4×5√2/5√2=4
j)=7√8×6√½=42√4=84
k)=2×3pierwiastki√3/6×3pierwiastki√3=⅓
l)=2×3pierwiastki√54/3×3pierwiastki√2=⅔×3pierwiastki√27=⅔×3=2
36)
a)=4√2+√2/√2=5√2/√2=5
b)=3√3-2√3/√3=1
c)=2×3pierwiastki√2+3×3pierwiastki√2/3pierwiastki√2=5
d)=√2(2√2+5√2)=7×√4=14
e)=2×5√2+6√2/2√2=8√2
f)=4×2×3pierwiastki√2-3×3pierwiastki√2/5×3pierwiastki√2=1
g)=5√10-4√10+2√10/10√10=3/10
h)=(2×3pierwiastki√3-3pierwiastki√3)×3pierwiastki√9=3pierwiastki√3×3pierwiastki√9=3pierwiastki√27=3